FAKTOR - FAKTOR YANG MEMPENGARUHI PERUSAHAAN MELAKUKAN AUDITOR SWITCH - SUSAN SUSAN; ESTRALITA TRISNAWATI (Jurnal Bisnis dan Akuntansi, 2011)
The purpose of this study is to analyze the factors that influence auditor switch to manufacturing companies listed in Indonesia Stock Exchange. These factors are change of management, accountant opinion, financial distress, public accountant firm’s size, and the percentage of the change of return on assets (ROA). The sample was selected using purposive sampling method. The company that used in this study consists of 44 companies for each period during 2004 - 2009. Hypothesis testing technique used logistic regression model. The result of this study show that change of management and public accountant firm’s size influencing auditor switch.